Ancient machinery embedded in the contemporary ribosome. (22nd March 2010) - Belousoff, Matthew J.; Davidovich, Chen; Zimmerman, Ella; Caspi, Yaron; Wekselman, Itai; Rozenszajn, Lin; Shapira, Tal; Sade-Falk, Ofir; Taha, Leena; Bashan, Anat; Weiss, Manfred S.; Yonath, Ada
Abstract : Structural analysis, supported by biochemical, mutagenesis and computational evidence, indicates that the peptidyltransferase centre of the contemporary ribosome is a universal symmetrical pocket composed solely of rRNA. This pocket seems to be a relic of the proto-ribosome, an ancient ribozyme, which was a dimeric RNA assembly formed from self-folded RNA chains of identical, similar or different sequences. This could have occurred spontaneously by gene duplication or gene fusion. This pocket-like entity was capable of autonomously catalysing various reactions, including peptide bond formation and non-coded or semi-coded amino acid polymerization. Efforts toward the structural definition of the early entity capable of genetic decoding involve the crystallization of the small ribosomal subunit of a bacterial organism harbouring a single functional rRNA operon.